Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Which of the following expressions is the inverse of the function y equals quantity x minus 2 divided by 3

Sagot :

The original equation is f(x)=(x-2)/3. And you need to inverse the x and y. The equation can be changed to: y=(x-2)/3 => x=(y-2)/3 => y=3x-2 =>f-1(x)=3x-2. So the answer is f-1(x)=3x-2.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.